Your evidence or mine? Systematic evaluation of reviews of marine protected area effectiveness. Issue 4 (29th November 2016) - Woodcock, Paul; O'Leary, Bethan C; Kaiser, Michel J; Pullin, Andrew S
Abstract: Marine protected areas (MPAs) are a key strategy for mitigating the impacts of fisheries, but their designation can be controversial, and there is uncertainty surrounding when and where MPAs are most effective. Evidence synthesis that collates primary research on MPA effectiveness can provide a crucial bridge between research, policy and practice. However, reviews vary in scope and rigour, meaning decision‐makers face the challenge of identifying appropriate reviews. Documenting differences amongst reviews can therefore support nonspecialists in locating the most relevant and rigorous reviews and can also assist researchers in targeting evidence gaps. We addressed these priorities by systematically searching for reviews examining effectiveness of MPAs for biodiversity, critically appraising methods used and categorizing review scope. The 27 reviews assessed overlapped in scope (suggesting some redundancy) and differed substantially in reliability. Key strengths related to the effects of MPAs on fish abundance and the influence of MPA size and age on effectiveness. However, several gaps were noted, with some questions not addressed and others lacking highly reliable syntheses – importantly, the latter may create the perception that particular questions have been adequately addressed, potentially deterring new syntheses. Our findings indicate key aspects of review conduct that could be improved (e.g. documenting critical appraisal of primary research, evaluating potential publication bias) and can facilitate evidence‐based policy by guiding nonspecialists to the most reliable and relevant reviews. Lastly, we suggest that future reviews with broader taxonomic coverage and considering the influence of a wider range of MPA characteristics on effectiveness would be beneficial.